Pengaruh Teknik Relaksasi Nafas Dalam terhadap Penurunan Nyeri pada Pasein Fraktur - Lela Aini; Reza Reskita (Politeknik Kesehatan Tanjung Karang, 2018)
Fracture is a crack on bones that is caused by trauma, or other physical energy so that the medical fracture patient will experience start from light until a heavy level of pain. According to data RSI Siti Khadijah Palembang, the number one of patients fractures tend to increase in 2016 as many 423 people. The aim of this study is to see whether there is or is not any breath relaxation technique in case of relieving the pain of fracture patients. This study is using the pre-experimental design in an involving a subject group, with One group Pretest-Posttest project. Sample taking technique is performed with Purposive Sampling method that consumes 30 respondents. This study is performed on 15th of June- 14th of July 2017 in RSI Siti Khadijah Palembang. The summary of the research shows that before the internal breath relaxation technique is done from 30 respondents, 10 of them experience the pain on scale of 4 as equal as (35,7%), either experience the reduction after the breath relaxation technique is done on scale of 2 and 3 each 8 respondents or as equal as (28,6%). The statistics test result that is using the Wilcoxon check (p-value=0.001) < α (0,05) is obtained which that means there is an effect of breath relaxation technique according to the pain revelation of medical fracture patients in RSI Siti Khadijah Palembang on 2017. With this study, it is expected that health workers can implement deep breathing relaxation techniques to reduce pain in fracture patients.